Cost-Effectiveness of Diphtheria Pertussis Tetanus Combo Vaccination - Imas Amalia Wardani; Didik Setiawan; Githa Fungie Galistiani (Riviera Publishing, 2025)
Backgrounds: To explain and systematically review the modelling and reporting of cost effectiveness analysis of vaccination DPT combo. Methods : We conducted a comprehensive and systematic review of cost-effectiveness studies related to vaccination DPT Combo and government immunisation programmes in the world published from 2000 to 2021, through database search of PubMed and Science Direct. We assessed the methodological quality of the selected studies using a specific approach Consolidated Health Economic Evaluation Reporting Standards checklist (CHEERS). Results : Eight eligible studies reporting comparative cost-effectiveness comparisons of vaccination DPT combination were identified. Every year the DPT combo vaccine always develops into more combinations, from single to combination with a composition of 6 types. The increasing development of the DPT combination vaccine means the costs incurred will be higher, but it will have better effectiveness and fewer repeat doses. Conclusion : The DPT Combination vaccine is a more complete combination for higher costs but with better effectiveness and lower side effects.